A multimodal imaging study of recognition memory in very preterm born adults. Issue 2 (20th September 2016) - Tseng, Chieh‐En Jane; Froudist‐Walsh, Seán; Brittain, Philip J.; Karolis, Vyacheslav; Caldinelli, Chiara; Kroll, Jasmin; Counsell, Serena J.; Williams, Steven C.R.; Murray, Robin M.; Nosarti, Chiara
Abstract: Very preterm (<32 weeks of gestation) birth is associated with structural brain alterations and memory impairments throughout childhood and adolescence. Here, we used functional MRI (fMRI) to study the neuroanatomy of recognition memory in 49 very preterm‐born adults and 50 controls (mean age: 30 years) during completion of a task involving visual encoding and recognition of abstract pictures. T1‐weighted and diffusion‐weighted images were also collected. Bilateral hippocampal volumes were calculated and tractography of the fornix and cingulum was performed and assessed in terms of volume and hindrance modulated orientational anisotropy (HMOA). Online recognition memory task performance, assessed with A scores, was poorer in the very preterm compared with the control group. Analysis of fMRI data focused on differences in neural activity between the recognition and encoding trials. Very preterm born adults showed decreased activation in the right middle frontal gyrus and posterior cingulate cortex/precuneus and increased activation in the left inferior frontal gyrus and bilateral lateral occipital cortex (LOC) compared with controls. Hippocampi, fornix and cingulum volume was significantly smaller and fornix HMOA was lower in very preterm adults. Among all the structural and functional brain metrics that showed statistically significant group differences, LOC activation was the best predictor of online task performance ( P  = 0.020). In terms of association between brain function and structure, LOC activation was predicted by fornix HMOA in the preterm group only ( P  = 0.020). These results suggest that neuroanatomical alterations in very preterm born individuals may be underlying their poorer recognition memory performance. Hum Brain Mapp 38:644–655, 2017 . ©2016 The Authors Human Brain Mapping Published by Wiley Periodicals, Inc.